Hubungan Tingkat Pengetahuan Dengan Kepatuhan Minum Obat Antihipertensi Pada Pasien Program Rujuk Balik (PRB) Di Puskesmas Kayu Tangi: Hubungan Tingkat Pengetahuan Dengan Kepatuhan Minum Obat Antihipertensi Pada Pasien Program Rujuk Balik (PRB) Di Puskesmas Kayu Tangi - Nur Fajriati; Darini Kurniawati; R. Topan Aditya Rahman (LPPM Universitas Sari Mulia, 2023)
Background: Hypertension is widely known as cardiovascular disease, where patients have blood pressure above normal, namely systolic blood pressure 140 mmHg and diastolic blood pressure 90 mmHg. Compliance with taking medication in patients with hypertension is very important because it can control blood pressure in patients with hypertension so as to prevent complications. The level of knowledge of hypertensive patients related to their disease can support the success of therapy so that the blood pressure of hypertensive patients can be well controlled Objective: Knowing the relationship between the level of knowledge and adherence to taking antihypertensive drugs in RP patients at the Kayu Tangi Health Center. Methods: This study used observational analytic with a Cross Sectional approach, data was collected prospectively using a knowledge questionnaire that had been tested for validity and reliability and a compliance questionnaire using the Morisky Medication Adherence Scale (MMAS-8). Results: This study obtained the results of the statistical test of the contingency coefficient with p value = 0.000 < 0.05, which means Ho is rejected and Ha is accepted. Conclusion: There is a relationship between the level of knowledge and adherence to taking antihypertensive drugs in patients with the Referback Program (RP) at the Kayu Tangi Health Center.